Extent of hematopoietic involvement by TET2 mutations in JAK2V617F polycythemia vera - Sabina I. Swierczek; Donghoon Yoon; Christine Bellanné-Chantelot; Soo Jin Kim; Cécile Saint-Martin; Francois Delhommeau; Albert Najman; Josef T. Prchal (Haematologica, 2011)
TET2 mutations are found in polycythemia vera and it was initially reported that there is a greater TET2 mutational burden than JAK2V617F in polycythemia vera stem cells and that TET2 mutations precede JAK2V617F. We quantified the proportion of TET2, JAK2V617F mutations and X-chromosome allelic usage in polycythemia vera cells, BFU-Es and in vitro expanded erythroid progenitors and found clonal reticulocytes, granulocytes, platelets and CD34+ cells. We found that TET2 mutations may also follow rather than precede JAK2V617F as recently reported by others. Only a fraction of clonal early hematopoietic precursors and largely polyclonal T cells carry the TET2 mutation. We showed that in vitro the concomitant presence of JAK2V617F and TET2 mutations favors clonal polycythemia vera erythroid progenitors in contrast with non-TET2 mutated progenitors. We conclude that loss-of-function TET2 mutations are not the polycythemia vera initiating events and that the acquisition of TET2 somatic mutations may increase the aggressivity of the polycythemia vera clone.